\(\sqrt{x^2+2\sqrt{x^2-1}}-\sqrt{x^2-2\sqrt{x^2-1}}\)

">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

8 tháng 10 2022

A = \(\sqrt{x^2+2\sqrt{x^2-1}}-\sqrt{x^2-2\sqrt{x^2-1}}\)

\(=\sqrt{\left(x^2-1\right)+2\sqrt{x^2-1}+1}-\sqrt{\left(x^2-1\right)-2\sqrt{x^2-1}+1}\)

\(=\sqrt{\left(\sqrt{x^2-1}+1\right)^2}-\sqrt{\left(\sqrt{x^2-1}-1\right)^2}\)

\(=\left(\sqrt{x^2-1}+1\right)-|\sqrt{x^2-1}-1|\)

\(TH1:|\sqrt{x^2-1}-1|=\sqrt{x^2-1}-1\)

\(\Rightarrow A=\sqrt{x^2-1}+1-\sqrt{x^2-1}+1\)

\(\Rightarrow A=2\)

\(TH2:|\sqrt{x^2-1}-1|=1-\sqrt{x^2-1}\)

\(\Rightarrow A=\sqrt{x^2-1}+1-1+\sqrt{x^2-1}\)

\(\Rightarrow A=2\sqrt{x^2-1}\)

14 tháng 7 2016

a/ \(A=\left(\frac{2\sqrt{x}+x}{\sqrt{x}^3-1}-\frac{1}{\sqrt{x}-1}\right):\frac{\sqrt{x}+2}{x+\sqrt{x}+1}\)

      \(=\left[\frac{2\sqrt{x}+x}{\left(\sqrt{x}-1\right)\left(x+\sqrt{x}+1\right)}-\frac{1}{\sqrt{x}-1}\right]:\frac{\sqrt{x}+2}{x+\sqrt{x}+1}\)

         \(=\frac{2\sqrt{x}+x-x-\sqrt{x}-1}{\left(\sqrt{x}-1\right)\left(x+\sqrt{x}+1\right)}.\frac{x+\sqrt{x}+1}{\sqrt{x}+2}\)

          \(=\frac{\sqrt{x}-1}{\sqrt{x}-1}.\frac{1}{\sqrt{x}+2}=\frac{1}{\sqrt{x}+2}\)

b/ Thay \(x=4+2\sqrt{3}\) vào A ta được:

    \(A=\frac{1}{\sqrt{4+2\sqrt{3}}+2}=\frac{1}{\sqrt{\left(\sqrt{3}+1\right)^2}+2}=\frac{1}{\sqrt{3}+3}\)

     \(\Rightarrow\sqrt{A}=\frac{1}{\sqrt{\sqrt{3}+3}}\)

23 tháng 5 2021

\(\frac{4+\sqrt{X}}{7}\)

30 tháng 7 2019

a) \(\sqrt{x-1-2\sqrt{x-2}}=\sqrt{\left(x-2\right)-2\sqrt{x-2}+1}=\sqrt{\left(\sqrt{x-2}-1\right)^2}=\left|\sqrt{x-2}-1\right|\)

b) \(\sqrt{x-2+2\sqrt{x-3}}-\sqrt{x-3}\)

\(=\sqrt{\left(x-3\right)+2\sqrt{x-3}+1}-\sqrt{x-3}\)

\(=\sqrt{\left(\sqrt{x-3}+1\right)^2}-\sqrt{x-3}=\sqrt{x-3}+1-\sqrt{x-3}=1\)

13 tháng 9 2016

a/ Ta có

P = \(\frac{1+\sqrt{x}}{\left(\sqrt{x}+1\right)\left(\sqrt{x}-1\right)}\) - \(\frac{2+x}{\left(\sqrt{x}-1\right)\left(x+\sqrt{x}+1\right)}\) - \(\frac{1+\sqrt{x}}{x+\sqrt{x}+1}\)

\(\frac{-\sqrt{x}}{1+\sqrt{x}+x}\)

14 tháng 9 2016

mình muốn hỏi câu b cơ bạn ơi